2019
DOI: 10.1128/jcm.01778-18
|View full text |Cite
|
Sign up to set email alerts
|

Heat Inactivation Renders Sputum Safe and Preserves Mycobacterium tuberculosis RNA for Downstream Molecular Tests

Abstract: The World Health Organization End Tuberculosis (TB) strategy has called for the development of—and increased access to—effective tools for diagnosis and treatment of TB disease. Mycobacterium tuberculosis , the causative agent of TB, is categorized as a highly infectious agent. Consequently, diagnostic tests that involve comprehensive manipulation of specimens from presumed tuberculosis cases must be performed in a category 3 laboratory. We have evaluated the use of heat inactivation to render TB samples safe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…As shown in table 3, the virus could not be detected in the event of heat treatment at 100°C for 30 mins, and 60 minutes, even if there is no statistical difference between the activated ones at 100°C for 10 mins and the non-inactivated samples. However, our study has shown that the virus loads measured in the heat-inactivated samples were consistent with those in the unheat-inactivated ones, with sufficient amounts of RNA preserved for downstream rRT-PCR testing, which concurs with the conclusions of Wilber Sabiiti et al and Boris Pastori et al [16][17][18] . The RNA preservation may be due to the preservation solution, which contains guanidine isothiocyanate, sodium dodecylsarcosine, and dithiothreitol.…”
Section: Rrt-pcr Results Of Inactivated At 100°csupporting
confidence: 90%
“…As shown in table 3, the virus could not be detected in the event of heat treatment at 100°C for 30 mins, and 60 minutes, even if there is no statistical difference between the activated ones at 100°C for 10 mins and the non-inactivated samples. However, our study has shown that the virus loads measured in the heat-inactivated samples were consistent with those in the unheat-inactivated ones, with sufficient amounts of RNA preserved for downstream rRT-PCR testing, which concurs with the conclusions of Wilber Sabiiti et al and Boris Pastori et al [16][17][18] . The RNA preservation may be due to the preservation solution, which contains guanidine isothiocyanate, sodium dodecylsarcosine, and dithiothreitol.…”
Section: Rrt-pcr Results Of Inactivated At 100°csupporting
confidence: 90%
“…In order to perform the test in a Biosafety Level 2 laboratory, samples were previously inactivated. MTBc inactivation was achieved using a dry-block at 95˚C for 30 minutes, this allowed easier and safer heat-inactivation compared to a boiling water bath, as previously shown by other Authors [16,17].…”
Section: Discussionmentioning
confidence: 72%
“…(i) RNA extraction. Extraction of RNA was performed as previously described (20,22). Briefly, 100 l of an extraction control (Vitalbacteria; SOI Group, UK) was added to each tube prior to RNA extraction.…”
Section: Confirmation Of M Tuberculosis In Liquid Culturementioning
confidence: 99%
“…Sequence-specific primers and TaqMan probes dually labeled for M. tuberculosis 16S rRNA and for the extraction control (EC) target were procured from MWG Eurofins, Germany. Master mix preparation, PCR test conditions, and ampli- fication were set and performed as previously demonstrated (19,20,22). The sensitivity and specificity of the primers and probes for MBLA were previously tested against nontuberculosis mycobacteria, including a wide range of respiratory pathogens, and none of them was found to be amplified (19).…”
Section: Confirmation Of M Tuberculosis In Liquid Culturementioning
confidence: 99%